Barthel Index as a Predictor of 1‐Year Mortality in Very Elderly Patients Who Underwent Percutaneous Coronary Intervention for Acute Coronary Syndrome: Better Activities of Daily Living, Longer Life. Issue 2 (31st December 2015) - Higuchi, Satoshi; Kabeya, Yusuke; Matsushita, Kenichi; Taguchi, Hiroki; Ishiguro, Haruhisa; Kohshoh, Hideyasu; Yoshino, Hideaki
ABSTRACT: Background: Percutaneous coronary intervention (PCI) is safe and effective in very elderly patients, defined as those who are age ≥85 years, with acute coronary syndrome (ACS). However, the prognostic factors remain unknown. The association between activities of daily living (ADL) and the prognosis after PCI has not yet been investigated. Hypothesis: Better ADL is associated with better 1‐year prognosis. Methods: This retrospective study included 91 consecutive very elderly patients with ACS. We calculated the Barthel Index (BI) as an indicator for ADL. Patients were classified into 2 groups according to BI: high BI (≥85) and low BI (<85). The BI was assessed both on admission (pre‐BI) and at discharge (post‐BI). Results: In the 91 patients (mean age, 88.2 ± 3.0 years, 52% male), 1‐year mortality was 33%. The Cox regression model demonstrated that low pre‐BI was not a risk factor for 1‐year mortality (hazard ratio: 0.73, 95% confidence interval [CI]: 0.30‐1.78, P  = 0.490). However, post‐BI was significantly associated with 1‐year mortality (hazard ratio: 0.25, 95% CI: 0.11‐0.57, P  = 0.001). The 1‐year mortality of the high and the low post‐BI group was estimated as 21% (95% CI: 12%‐35%) and 62% (95% CI: 42%‐82%), respectively. A 5‐unit decrease in post‐BI was related to a 1.10‐fold increased risk for 1‐year mortality (95% CI: 1.05‐1.15, P  < 0.001). Conclusions: Activities of daily living at discharge, although not before admission, may be a useful predictor for 1‐year mortality in very elderly patients undergoing PCI for ACS.